Perbandingan Panas dalam Implementasi Sistem Efek Rumah Kaca dan Sistem Tradisional pada Pengeringan Biji Kopi - Amiruddin Amiruddin; Hendi Lilih Wijayanto; Kadriadi Kadriadi; Kadex Widhy Wirakusuma (Universitas Batanghari Jambi, 2022)
Indonesia as a country with the largest tropical climate in the world after Brazil, from 27 percent of the tropical zones in the world, Indonesia has 11 percent of tropical areas, including South Sulawesi which is a coffee-producing area which has an area of 690,283 hectares (ha) consisting of People's Plantations 656,067 ha. (95%), Private Basar plantations 19,077 (2.8%), State Large Plantations 15,139 ha (2.2%), South Sulawesi coffee producing areas, especially in Bantaeng spread across Tompo Bulu District. Most of the coffee in Bantaeng is grown in a mixed garden system. However, the drying process has a relatively long time span, so that the coffee harvest has a low level of dryness and the selling price is also not optimal. From these problems, the authors compare the temperature in the dryer with the greenhouse effect system and traditional drying, which is 10% - 30% degrees Celsius hotter using the greenhouse effect. For the efficiency level, the drying time between the greenhouse effect system and traditional drying is about 5-12 days faster using the greenhouse effect drying system.